PENGARUH PELATIHAN KERJA TERHADAP PENINGKATAN KUALITAS KINERJA ROOM ATTENDANT DI HOTEL BEST WESTERN PREMIER PANBIL BATAM - Syafira Tamara; Zahara Fatimah; Frangky Silitonga (JURNAL MEKAR, 2023)
This study aims to determine the effect of job training on the performance quality of room attendants at the Best Western Premier Panbil Hotel, Batam City. This type of research uses quantitative methods. The population and sample in this study were all Room Attendant Housekeeping employees. The sample collection technique used in this study uses a saturated sampling technique. The method used in testing the hypothesis includes using. Validity Test, Reliability Test, Normality Test, Linearity Test, T (Partial) Test, and using Simple Linear Regression Analysis. The data obtained is data that is the result of the respondent's answers to the questionnaires distributed. The results of this study indicate that there is a significant influence between job training on improving the quality of room attendant performance. The results of R square found that job training variables affect the performance of room attendant employees by 72.8%, and the remaining 28.2% is influenced by other factors outside the observed variables. Suggestions for the Best Western Premier Panbil Hotel, this final project research can be used as a reference or reference material by the hotel where the author's research pays more attention to the needs and performance of room attendants